THE INTERSECTION OF PHILOLOGY AND DIGITAL HUMANITIES - Choriyeva Mohina Hakim qizi (Web of Journals Publishing, 2025)
The intersection of philology and the digital humanities represents a revolutionary union that enhances our understanding of language, literature, and culture through time. The cross-fertilization of traditional philological practices with sophisticated digital technologies and methodologies enables scholars to study massive corpora, visualize linguistic patterns graphically, and engage with historical texts in unprecedented ways. This article explores the implications for language and literature as a discipline from this integration, with case studies showing the new approaches utilized within this blended field. The potential of digital humanities to democratize access and interdisciplinarity also makes this an essential part of scholarship in the present. Lastly, this intersection opens up new research avenues, deepening our knowledge of cultural heritage and widening the field of both research fields.
Keywords: Philology, digital humanities, language studies, textual analysis, cultural heritage, interdisciplinary collaboration.